(untitled) (The Journal of Research ANGRAU, 2026)
A research trial was conducted in clay loam soils at Regional Agricultural Research Station, Maruteru, Andhra Pradesh during rabi, 2022-23 to assess the effects of puddling and crop establishment methods on rice productivity.The study comprised two factors: puddling practice, viz., power tiller (M1 ), rotovator (M2 ,) and roto-puddler (M3 ) as main plot treatments and crop establishment method, viz..,drum seeding (E1 ),line planting (E2 ),machine planting (E3 ),diagonal planting (E4 ,) and Bengal planting (E5 ) as sub-plot treatments.The results showed that among the puddling practices, the use of a roto-puddler registered the highest growth parameters at harvest, such as number of tillers m-2 (401), crop dry matter (11053 kg ha-1), and yield attributes, that is, the number of panicles m-2 (371), total number of grains panicle-1 (259), grain (4697 kg ha-1), and straw yield (6098 kg ha-1). This was statistically at par with the use of a rotovator but significantly superior to that of a power tiller. Among crop establishment methods, growth parameters at harvest, that is, number of tillers m-2 (416), crop dry matter (11427 kg ha-1), and yield parameters, that is, the number of panicles m-2 (386), total number of grains panicle-1 (257), grain (4837 kg ha-1), and straw yield (6148 kg ha-1) were higher with the diagonal planting method; however, it was found statistically at par with Bengal planting and drum seeding but significantly superior over machine planting and line planting.